Effectiveness of Ginger Patch Therapy in Reducing Back Pain in Third Trimester Pregnancy - Uly Artha Silalahi; Wiwin Mintarsih Purnamasari; Yeni Marliani (Midwifery Department, Poltekkes Kemenkes Denpasar, Indonesia, 2026)
Lower back pain is a common complaint among third-trimester pregnant women due to physiological and postural changes during pregnancy. If not properly managed, this condition may reduce maternal comfort and daily activity. Ginger patch therapy is a non-pharmacological intervention that provides a warming effect and analgesic properties to relieve pain. This study aimed to analyze the effect of ginger patch application on lower back pain intensity among third-trimester pregnant women in the working area of UPTD Puskesmas Cisayong. A quantitative pre-experimental study with a one-group pretest–posttest design was conducted involving 19 pregnant women selected using accidental sampling. Pain intensity was measured using the Numeric Rating Scale before and after the intervention. Data analysis included univariate analysis and bivariate analysis using the Wilcoxon Signed Rank Test with a significance level of p < 0.05. The results showed a decrease in the mean pain score from 7.53 before the intervention to 2.42 after the intervention. Statistical analysis indicated a significant effect of ginger patch application on pain reduction (p = 0.000). These findings indicate that ginger patch therapy is effective in reducing lower back pain among third-trimester pregnant women and can be recommended as a safe and practical complementary therapy during pregnancy.